PENGARUH TANGGUNGJAWAB RUMAH TANGGA MAHASISWA MENIKAH TERHADAP PRESTASI AKADEMIK (Studi Kasus Pada Sekolah Tinggi Agama Islam MA Bayang) - Jurna Petri Roszi; Zidni ‘Ilman Nafi’an; Hamda Sulfinadia (UIN Imam Bonjol Padang, 2021)
This study aims to analyze the effect of household responsibilities from the perspective of personality, motivation, cognition and work responsibility on the academic achievement of married students at the MA Bayang Islamic High School. This research approach is quantitative research with survey method and cross sectional design. The research population is all married students who are registered as active students of the 2018 Islamic High School MA Bayang. Samples were taken by accidental sampling technique as many as 40 people. The research instrument used observation sheets, questionnaires, interviews and documentation. The author's data collection techniques use observation, questionnaires, and documentation. While the data analysis technique the author presents in the form of data tabulation techniques and processed with SPSS version 16 computational techniques, then the data that has been processed is interpreted and analyzed. Questionnaire data was analyzed using the percentage equation to calculate the Total Respondent Achievement (TCR), while the inferential data was calculated using Multiple Linear Regression. From the results of the study, it was found that the personality/attitude of married students in household responsibilities had an average index of 3.24 and the level of achievement of respondents was 64.8% with a good enough category, a significant effect on academic achievement of 0.032, while motivation (college support from partners in household) the average index is 3.22 and the level of achievement of respondents is 64.3% with a fairly good category, it does not significantly affect academic achievement where the value of b is -0.013, and cognition of household students with an average index of 3.21 with the level of achievement of respondents 64.3%, has a significant effect on academic achievement, where the value of b is 0.025.